Asymmetry of Height and Width of Ethmoid Sinus and Its Association with Chronic Sinusitis: A Cross Sectional Study: - Majidi, Shima; Mousaviagdas, Mehrnoosh; Shahidi, Nikzad; Khamnian, Zhila (Galen Medical Journal, 2020)
Background: In this study, we aimed to investigate the association between chronic anterior sinusitis with the width and height of ethmoid sinus and also assess the ethmoid length and roof asymmetry in the Iranian adult population. Materials and Methods: This cross-sectional study was carried out on 422 patients who were referred with clinical signs of rhinosinusitis to the ENT Center of Tabriz University of Medical Sciences. Study participants were divided into healthy and sinusitis groups based on the level of sinus involvement. Computed tomography images were applied to calculate ethmoid height and width. A paired t-test was used to assess the roof and width asymmetry and an independent t-test was used to investigate the association between ethmoid height and width with the incidence of rhinosinusitis. Results: The mean age of sinusitis and healthy groups was 42.5Â±18.9 and 38.4Â±17.1 years, respectively. Of a total 422 subjects, 63.4% of whom were men. The overall prevalence of rhinosinusitis was 28.0%. We observed a statistically significant difference in terms of ethmoid height, and in both healthy and sinusitis group right ethmoid roof was statistically lower (P<0.05). However, no statistical difference was observed between the left and right side regarding the ethmoid sinus width (P>0.05). We also estimated correlation coefficients for rhinosinusitis score and ethmoid sinus height and width, which were not statistically significant (P>0.05). Conclusion: Our study shows that the right side of the ethmoid roof was lower in comparison to the left side, and it should be fully understood and regarded in rhino sinus surgery. We also observed no association between sinusitis score and height and width of the ethmoid sinus. [GMJ.2020;9:e1748]